2001
DOI: 10.1111/j.1550-7408.2001.tb00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Riding The Ciliate Cell Cycle—A Thirty‐Five‐Year Prospectivea

Abstract: Studies of the ciliate cell cycle have moved from early examination of its biochemistry with heat-synchronized Tetrahymena through descriptive studies of Paramecium using small synchronous cell samples. These studies described what happens during the cell cycle and provided some initial insights into control, especially the idea that there was a point at which cells became committed to division. This early work was followed by an analytical phase in which the same small sample techniques, combined with gene mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Iwamoto et al (2004) suggested that Tetrahymena thermophila (a nonrumen ciliate) senses its cell volume or macronuclear DNA concentration and coordinates this regulation with nutrient supply and transfer. If not coordinated with transfer (and sudden dilution of cell numbers relative to substrate provision), checkpoints in the cell cycle should subsequently arrest cell division (Berger, 2001). Thus, while verifying reasons for changes in 18S rDNA copies among protozoal standards for use as a biomass marker, 18S rDNA also was hypothesized to be an ideal indicator to evaluate shifts in growth rates among rumen ciliates in cultures undergoing different dietary treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Iwamoto et al (2004) suggested that Tetrahymena thermophila (a nonrumen ciliate) senses its cell volume or macronuclear DNA concentration and coordinates this regulation with nutrient supply and transfer. If not coordinated with transfer (and sudden dilution of cell numbers relative to substrate provision), checkpoints in the cell cycle should subsequently arrest cell division (Berger, 2001). Thus, while verifying reasons for changes in 18S rDNA copies among protozoal standards for use as a biomass marker, 18S rDNA also was hypothesized to be an ideal indicator to evaluate shifts in growth rates among rumen ciliates in cultures undergoing different dietary treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrahymena is widely employed as a model system to study morphogenesis, conjugation, cell division, growth kinetics, membrane biogenesis, and membrane adaptation (Berger et al2001; Nakashima et al 1996; 1997; Turkewitz, Orias, and Kapler 2002; Wang et al 1998; 1999). As an initial step to understand the role of SPHK in Tetrahymena , changes in SPHK activity were first examined during different stages of culture growth.…”
Section: Resultsmentioning
confidence: 99%
“…Cell size (Wichterman, 1953;Berger, 2001), serotype (Preer Jr, 1986;Bleyman, 1996) and clonal life span (Takagi et al ., 1987a) are examples in Paramecium . The present study of the autogamy-maturation pattern added another example.…”
Section: Discussionmentioning
confidence: 98%